Routledge Handbook of the Global History of Warfare - Roy, Kaushik, 1971-; Charney, Michael W. (London: New York: Routledge, Taylor & Francis, 2024)
"This handbook examines key aspects of the development of the global history of warfare and the changing patterns of warfare over time. Although scholarship has long eschewed a chronological narrative of the evolution of warfare that privileges the Western experience, global histories of warfare have had difficulty avoiding an overemphasis on the West. The present volume is a collection of themes rather than a history per se; it provides important perspectives on the emergence of warfare as a global historical experience from the ancient past to the present-day. Drawing together numerous experts, it tells a broader, more inclusive story of the global, human experience with wars and warfare. The 35 essays are organized in eight thematic sections: Part I: Origins of Warfare Part II: Polities and Armed Forces in the Pre-modern Era Part III: Steppe Nomads of Eurasia Part IV: Naval Warfare and Piracy in the Pre-Industrial World Part V: The Impact of Gunpowder Part VI: Transition from Industrial to Total War Part VII: Wars of Decolonisation and Cold War Part VIII: Postmodern/New Wars These sections offer an overview of the global experience of warfare to help readers understand how the wars and the militaries we see today have been shaped by historical developments across the globe. This handbook will be of great interest to students of military history, naval history, strategic studies and world history in general"--
Introduction: The evolution of warfare : global perspectives / Kaushik Roy and Michael W. Charney -- The evolution of Bronze Age warfare, and its historical significance, in Western Eurasia and the Near East / Robert Drews -- War, captive-taking, and warriors in Pre-Columbian Mesoamerica / Andrew K. Scherer -- Indigenous warfare in Australia and New Zealand / John Connor, Michael W. Charney, and Kaushik Roy -- Assyrian warfare, 1550-609 BCE / Sarah C. Melville -- The polis and the emergence of Hoplite warfare / Matthew Trundle -- Transition from Roman to Merovingian warfare : The long fifth century / Bernard S. Bachrach -- New approaches to late Imperial Chinese warfare / Kenneth M. Swope -- Warfare in precolonial Africa / O.R. Coates -- The European Huns / Cameron Barnes -- Arab-Byzantine warfare: 660 CE-1040 CE / John Haldon -- Crusading armies and the Turks in the Middle East / John D. Hosler -- The limits of Mongol military power / Timothy May -- The cycle of empire in Central Asia : the frontier and beyond / Andrew de la Garza -- The Egyptian origins of amphibious warfare: Out of Africa / Mark Charles Fissel -- China's pirate wars, 1522-1810 / Robert J. Antony -- Rise of British naval power in the Indian Ocean / Amarendra Kumar -- Economy and gunpowder weapons in Western and Central Europe / Philip T. -- Hoffman -- Gunpowder and the rise of Muscovy : circa 1200-circa 1800 / Kaushik Roy -- Smallpox and war in America / Erica Charters -- Gunpowder and the North American Indian way of war / Kaushik Roy -- Firearms and maritime gunpowder states of Asia / Michael W. Charney -- Napoleon and mass warfare / Andrew Bamford -- The American Civil War and the beginning of total war? / A. James Fuller -- The British Army, 1870-1918 : from small war to trench war / Ian F. W. -- Beckett -- Theory and practice of armoured war during the two World Wars / Michael W. Charney -- Race and conflict in the Asia-Pacific region : 1941-1945 / Mark Johnston -- Modern naval warfare : 1815-2000 / Andrew Lambert -- Strategic air power in the two World Wars / Kathryn Barbier -- Warfare in the Middle East since 1945 / Rob Geist Pinfold -- Wars of decolonisation in South Asia : the Indian Army, 1945-47 / Alan Jeffreys -- The Falklands conflict : the last British Imperial war? / Rob McLaughlin -- The global War on Terror : the American operations in Afghanistan and Iraq / -- Robert Johnson -- Private military contractors and conflicts in the New Millennium / Christopher Kinsey -- The arms race in contemporary East Asia / Andrew T.H. Tan -- Employment of air power in fourth generation warfare : an Indian perspective / Air Vice Marshal Arjun Subramaniam.
Includes bibliographical references and index.
Keywords: Military art and science -- History